Response of ants to grazing disturbance at the central Monte Desert of Argentina: community descriptors and functional group scheme - Claver, Silvia (2014)
Livestock ranching is one of the main productive activities in arid regions of the world. Grazing produces changes in animal as well as plant communities (e.g. richness, abundance and species dominance relationships). Ants are good biological indicators due to the environmental fidelity of some of their community parameters. We described the functional structure of the ant community in the central Monte of Mendoza, Argentina, and examined the effect of grazing using richness, diversity and the functional group scheme. We used pitfall traps to sample ants at a reserve with 30-year cattle exclusion and at an adjacent ranch. Eleven of the 27 recorded species showed significant differences in their abundance and two species were absent at the ranch. While richness and diversity did not reflect these differences, functional groups did. Hot Climate Specialists were more abundant at the ranch while Cryptic Species and Generalized Myrmicinae increased at the reserve. This study supports the utility of the functional group scheme to study the effects of grazing disturbance in ant communities of arid regions.